1983
DOI: 10.1111/j.1476-5381.1983.tb10489.x
|View full text |Cite
|
Sign up to set email alerts
|

Neurotensin and antinatriuresis in the conscious rabbit

Abstract: The mechanism of alteration in renal sodium excretion in response to dietary changes is complex and poorly understood. A gut ‘sensor’ might exist which regulates the renal response and this may involve one or more of the now ubiquitous gastrointestinal peptides. Several of these gut peptides, including neurotensin, have been found within the kidney. Plasma levels of neurotensin, which is both a circulating hormone and putative neurotransmitter, rise promptly on feeding. When infused into the conscious rabbit, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

1987
1987
2025
2025

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…These observations collectively suggest that N T could function as a circulating hormone. Hence, the renal effects of N T demonstrated in the present as well as previous studies (Bloom et al 1983;Unwin et a / . 1987) lend support to the speculation that N T may be a mediator of the influence of gastrointestinal tract on renal excretion of sodium and water.…”
Section: Discussionsupporting
confidence: 88%
“…These observations collectively suggest that N T could function as a circulating hormone. Hence, the renal effects of N T demonstrated in the present as well as previous studies (Bloom et al 1983;Unwin et a / . 1987) lend support to the speculation that N T may be a mediator of the influence of gastrointestinal tract on renal excretion of sodium and water.…”
Section: Discussionsupporting
confidence: 88%
“…Neurotensin plasma levels rise promptly in response to feeding. In conscious rabbits, neurotensin produces a dose-related fall in renal sodium excretion (54). It has also been shown that neurotensin and vasoactive intestinal polypeptide (VIP) reduce blood pressure and natriuresis, followed by a dose-related fall in plasma ANP (6).…”
Section: Neurotensinmentioning
confidence: 99%
“…It acts as a paracrine and endocrine modulator of digestive functions in the gut (Ferris, 1989). It is located in specific glandular cells, called the N cells, and may be released into the blood after food ingestion, thus influencing not only the digestive system (Mashford et al , 1978; Blackburn et al , 1980; Croci et al , 1995a), but presumably the cardiovascular system and renal functions too (Quirion et al , 1982; Bloom et al , 1983; Unwin et al , 1987; Kivlighn & Jandhyala, 1990; Nisato et al , 1994). NT has antidiuretic action after i.v.…”
Section: Introductionmentioning
confidence: 99%